'All across Europe it had come': The Black Death and Fascism in Sylvia Townsend Warner's The Corner That Held Them. Issue 1 (10th November 2021) - Piette, Adam
Abstract : page_13 other Sylvia Townsend Warner's wartime novel The Corner that Held Them (1948), about a nunnery during the Black Death, reflects on female community and bonding in a period of male fascist violence. The novel explores the shift from pacifism to acceptance of the need for anti-fascist war which characterised Warner's intellectual beliefs from the 1930s into wartime, probing the arts of peace in compositional practice. Such a dialectic of war and peace is considered in relation to what Maud Ellmann has described as the outward turn to collective choral consciousness in mid-century modernism. This article explores both the staging of fascism as plague and the feminist daring and limits that Warner saw as operative in female witnessing and withstanding of Nazi ideology and menace. It closely reads key scenes from the panorama of a novel (notably Alianor's stillness as her husband is killed, Alicia's plans to withstand the economic impact of the Black Death and the cure of Ralph's plague symptoms) to register the satirical and allegorical substance of Warner's rescripting of Woolfian notions of resistance to warmongering misogyny by a society of outsiders. The readings seek to consolidate a varied and multiple sense of the book as a Marxist historical novel that gives voice to the ruled. In doing so Warner analyses the Black Death as a moment in history that saw the emergence of early modern capitalism and labour relations out of the feudal system, page_14 other even as the religious framework that had structured medieval Europe gave way to more secular beliefs in autonomy, self-determination, citizen and collective dreams, projects and affects. At the same time the plague as a political trope, rooted in anti-fascist rhetoric that turns Nazi anti-Semitic uses of the Black Death motif on their head, triggers readings that bring those historical scenes into allegorical relation with the ways in which the Second World War was experienced by marginalised female communities.